2016
DOI: 10.1093/molbev/msw057
|View full text |Cite
|
Sign up to set email alerts
|

Independent and Parallel Evolution of New Genes by Gene Duplication in Two Origins of C4 Photosynthesis Provides New Insight into the Mechanism of Phloem Loading in C4 Species

Abstract: C4 photosynthesis is considered one of the most remarkable examples of evolutionary convergence in eukaryotes. However, it is unknown whether the evolution of C4 photosynthesis required the evolution of new genes. Genome-wide gene-tree species-tree reconciliation of seven monocot species that span two origins of C4 photosynthesis revealed that there was significant parallelism in the duplication and retention of genes coincident with the evolution of C4 photosynthesis in these lineages. Specifically, 21 orthol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
80
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 73 publications
(93 citation statements)
references
References 72 publications
4
80
1
Order By: Relevance
“…(a) Phylogenetic relationship between putative orthologs in the following grasses: Zea mays L., Sorghum bicolor , Setaria italica , Hordeum vulgare, Triticum urartu (progenitor of A‐genome of bread wheat Triticum aestivum ), Brachypodium distachyon and Oryza sativa . Chronogram branch divergence time‐points are in million years (Emms et al ., ). Red dots represent the number of SWEET 13 paralogs for each species.…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…(a) Phylogenetic relationship between putative orthologs in the following grasses: Zea mays L., Sorghum bicolor , Setaria italica , Hordeum vulgare, Triticum urartu (progenitor of A‐genome of bread wheat Triticum aestivum ), Brachypodium distachyon and Oryza sativa . Chronogram branch divergence time‐points are in million years (Emms et al ., ). Red dots represent the number of SWEET 13 paralogs for each species.…”
Section: Resultsmentioning
confidence: 97%
“…Recently, ZmSWEET13 had been implicated as a possible key player in C 4 -photosynthesis in grasses (Emms et al, 2016). To test their role in maize, we designed guide RNAs that target a conserved region within a transmembrane domain, assuming that defects in the membrane domain would lead to complete loss of function.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, until recently the lack of genome sequences for closely related C 3 and C 4 species precluded accurate assessments of these phenomena, and so evidence for gene duplication followed by neofunctionalization playing a major role in the evolution of core C 4 genes was lacking [33 -35]. Subsequently, approaches that accurately localized gene duplication events across gene families [36,37] have revealed that in monocotyledons, many C 4 cycle genes appear to have duplicated in the last common ancestor of lineages containing C 4 plants [38]. There is also evidence that C 4 photosynthesis is built on pre-existing components.…”
Section: The Biochemistry and Evolution Of C 4 Photosynthesismentioning
confidence: 99%
“…This, together with the typically higher photosynthetic 97 CO2 uptake rate in C4 leaves compared to C3 leaves, C4 photosynthesis demands a much 98 higher capacity for metabolite transport between the two compartments (Hatch and 99 Osmond, 1976;von Caemmerer and Furbank, 2003). Indeed, a number of transporters on 100 chloroplast envelope, including PEP transporter (PPT), pyruvate transporter (BASS2), 101 and malate transporter in MC (DIT1), all show much higher transcript abundance in C4 102 species than in C3 species (Emms et al, 2016;Lyu et al, 2018;Moreno-Villena et al, 103 2018). Identifying the C4 paralogs of individual metabolite transporters, understanding 104 their evolutionary trajectories and the molecular mechanisms behind the increased 105 abundance or capacity of these transporters are major research focuses of the current C4 106 photosynthesis research.…”
mentioning
confidence: 99%